FIA– Spectrophotometric methods for the determination of Naringenin in supplements and urine samples using diazotization coupling reactions - ALmashhadani, Israa M. Jawad; Abed, Sadeem Subhi (Iraqi Journal of Science, 2018)
Direct FIA methods for estimation of Naringenin (NG) in different samples were proposed. These methods are based on diazotization coupling reactions of two reagents: method (A) p-chloroaniline (PCA) and method (B) procaine hydrochloride (PRH) with NG in basic medium. Yellow dyes with maximum absorption at 416 and 415 nm were formed respectively. Calibration curves were constructed over different NG concentrations, linearity was from 1- 70 and 1- 40 µgmL-1 with detection limits of 0.55 and 0.24 µgmL-1 for (A) and (B) respectively. All analytical variables involved in the FIA procedure were evaluated and optimized. The established methods were successfully applied for the determination of NG in its supplements and urine samples.